2022
DOI: 10.1186/s12967-021-03210-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased burden of cardiovascular disease in people with liver disease: unequal geographical variations, risk factors and excess years of life lost

Abstract: Background People with liver disease are at increased risk of developing cardiovascular disease (CVD), however, there has yet been an investigation of incidence burden, risk, and premature mortality across a wide range of liver conditions and cardiovascular outcomes. Methods We employed population-wide electronic health records (EHRs; from 1998 to 2020) consisting of almost 4 million adults to assess regional variations in disease burden of five li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 73 publications
(48 reference statements)
1
10
0
Order By: Relevance
“…Among the biomarkers associated with increased odds of respiratory treatment, five of them (high-density lipoprotein cholesterol, c-reactive protein, triglycerides, haemoglobin, and Clauss fibrinogen) are risk factors for cardiovascular disease (CVD), and two of them (glycated haemoglobin and alkaline phosphatase) are risk factors for diabetes and liver disease, respectively. The link between liver disease and CVD and diabetes and CVD has been confirmed in previous studies [ 22 , 23 ]. Recent studies have also demonstrated the association between CVD, liver disease, diabetes, and respiratory viral infections (e.g., COPD and COVID-19) [ 24 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 72%
“…Among the biomarkers associated with increased odds of respiratory treatment, five of them (high-density lipoprotein cholesterol, c-reactive protein, triglycerides, haemoglobin, and Clauss fibrinogen) are risk factors for cardiovascular disease (CVD), and two of them (glycated haemoglobin and alkaline phosphatase) are risk factors for diabetes and liver disease, respectively. The link between liver disease and CVD and diabetes and CVD has been confirmed in previous studies [ 22 , 23 ]. Recent studies have also demonstrated the association between CVD, liver disease, diabetes, and respiratory viral infections (e.g., COPD and COVID-19) [ 24 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 72%
“…While higher levels of ALT and other markers of liver dysfunction have been linked to higher CVD risk, this link has been found in populations where ALT largely rises alongside with obesity and other common CVD risk factors (26,27), as is observed in the concordant pro le in our study. However, recent large-scale meta-analyses have shown evidence of independent inverse associations between ALT and CVD risk in individuals with ALT levels in the normal range (28,29), as well as in alcoholic and non-alcoholic liver disease (30). Accordingly, while higher ALT was positively associated with risk of diabetes-related CVD, it was inversely associated with CVD risk not related to diabetes (31).…”
Section: Discussionmentioning
confidence: 99%
“…We utilised openaccess electronic health record phenotypes (https://phenotypes. healthdatagateway.org) that had been validated 3,18,[31][32][33] . The 144 conditions were classified into 12 organ systems.…”
Section: Site-specific Cancers Health Conditions and Treatment Exposuresmentioning
confidence: 99%